2017
DOI: 10.1186/s13005-017-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between interleukin-28B gene polymorphisms as a potential biomarker and the risk of chronic Periodontitis in an Iranian population

Abstract: BackgroundChronic Periodontitis (CP) is a common inflammatory disease affects supporting tissues of the teeth and can lead to tooth loss. The objective of this study was to determine the relationship between polymorphisms in the IL-28B gene and chronic periodontitis in an Iranian population.MethodsTwo hundred and ten CP patients and one hundred healthy subjects were enrolled in the present case-control study. The rs12979860 and rs8099917 SNPs were identified using RFLP and T-ARMS-PCR methods respectively.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(69 reference statements)
0
4
1
Order By: Relevance
“…This finding indicates that the mentioned factors do not affect the difference between target and measured curves. Heidari and Sagheb (2006) showed that Fars and Baluch children are different regarding head and face type indicators, phenotypes [17], and the effectiveness of the factors mentioned above in the results of real-ear measurements [14]. Nevertheless, the results of the current study indicated no significant difference between Fars and Baluch children in terms of predicted and measured curves.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This finding indicates that the mentioned factors do not affect the difference between target and measured curves. Heidari and Sagheb (2006) showed that Fars and Baluch children are different regarding head and face type indicators, phenotypes [17], and the effectiveness of the factors mentioned above in the results of real-ear measurements [14]. Nevertheless, the results of the current study indicated no significant difference between Fars and Baluch children in terms of predicted and measured curves.…”
Section: Discussioncontrasting
confidence: 50%
“…In terms of anatomical features of the ear, the outer ear of girls and women is smaller than boys and men [15,16]. Regarding head and face, there is a difference between the two Iranian populations of Fars and Baluch [17,18]. In addition, the asymmetry between the dimensions of the two ears has been reported in some studies [19,20].…”
mentioning
confidence: 99%
“…A genomic investigation by Zahra et al, found a connection between periodontal infection and two single nucleotide polymorphisms of IFN-λ2, rs8099917 and rs12979860. 56 As reported by Shivaprasad et al, patients with periodontitis have more IFN-λs levels than periodontally healthy people do. 57 Additional researches by Shivaprasad et al, show that IFN-λ1 is highly expressed in the aggressive form of periodontitis, whereas IFN-λ2 in chronic form.…”
Section: S 75mentioning
confidence: 86%
“…The reason for this discrepancy can be due to the ethnic differences between the studied populations and other differences in sample size and age groups. Smoking has been identified as a major environmental risk factor associated with increased incidence and severity of periodontitis 15 . Thus, smokers were excluded from our study to have less confounding factors when analyzing any genetic association with periodontitis.…”
Section: Discussionmentioning
confidence: 99%